The Role Of Digital Culture In Mediating The Influence Of Workload And Management Information Systems On Employee Performance - Indriastuti, Ratih; Ida Ayu Oka Martini (Amkop Management Accounting Review (AMAR), 2025)
This study aims to determine the effect of workload on the performance of the work, the influence of management information systems on employee performance, the effect of workload on digital culture, the influence of management information systems on digital culture, the influence of management information systems on employee performance through digital culture, the influence of management information systems on employee performance through digital culture, the influence of digital culture on employee performance. The conclusion of this study is the workload affects employee performance. This means that both the workload felt by employees will affect employee performance behavior. Management information system affects employee performance. This means that both the management information system felt by employees will affect employee performance behavior. Workload affects employee digital culture. This means that both the workload felt by employees will affect the employee's digital culture. The management information system does not affect employee digital culture. This means that the management information system that employees feel by will not affect the employee's digital culture. Digital culture strengthens the effect of workload on employee performance. This means that the existence of digital culture has an impact on increasing employee performance behavior caused by workload. Digital culture does not strengthen the effect of management information systems on employee performance. This means that the existence of digital culture does not have an impact on increasing employee performance behavior caused by management information systems. Digital culture affects employee performance. This means that both digital culture that employees feel by will affect employee performance behavior.